Biomonitoring of polycyclic aromatic hydrocarbons (PAHs) from Manila clam Ruditapes philippinarum in Laizhou, Rushan and Jiaozhou, bays of China, and investigation of its relationship with human carcinogenic risk. (November 2020) - Sun, Jiawei; Pan, Luqing; Cao, Yunhao; Li, Zeyuan
Abstract: This study examined the marine environment and seafood safety using chemical monitoring and multiple biomarkers. Samples were collected from three bays on the Shandong Peninsula in China, Laizhou, Rushan and Jiaozhou, in March, May, August, and October of 2018 and 2019. The polycyclic aromatic hydrocarbon (PAH) concentrations in sediments and tissue samples from the clam Ruditapes philippinarum and multiple biomarkers were measured. All the sampling sites were found to be medium-PAH-contaminated areas (100–1000 ng/g d.w.). According to the correlation analysis, ethoxyresorufin-o-deethylase (EROD) and superoxide dismutase (SOD) activity in the clam's digestive gland were sensitive to PAHs (p  < .05), but the incremental lifetime cancer risk (ILCR) was lower than the priority risk level (10 −4 ) at most sampling sites. EROD, SOD and acetylcholinesterase activity exhibited significant correlations with the ILCR values (p  < .01), suggesting that they may serve as good indicators for assessing safe seafood consumption levels for human beings. Highlights: Seasonal effects on the biomarker response of Manila clam were studied. EROD and SOD were reliable biomarkers for monitoring PAH pollution. The correlation of ILCR with the biomarker responses was verified ( p  < .01).